2018
DOI: 10.1111/jpn.13049
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial impacts of bee pollen in animal production, reproduction and health

Abstract: Bee pollen (BP) is one of the most useful therapeutic products favoured by natural medicine scientists because of its possible nutritional and medical applications. It exhibits many impacts such as antimicrobial, immunostimulating, antioxidants and hepatoprotective. Furthermore, BP has some useful therapeutic features in numerous pathological situations such as its impact to normalize wound healing. Based on previous literatures, the level of BP supplement in livestock and poultry ranged from 0.1 to 20 g/kg di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 27 publications
1
46
0
1
Order By: Relevance
“…In this sense, worker bees use pollen for royal jelly production (basic food for the larval queen and worker larvae) or directly as food due to the great amount of proteins and lipids present in it [2]. As it immensely benefits the insects' diet, pollen has become an important component of animal feed, above all, as an exceptional source of proteins and a good natural substitute for antibiotics [3]. Regarding pollen as food for humans, the first review was probably presented in the 70s; the authors [2] had reviewed the currently available data and concluded that for some athletes from different countries pollen as a dietary supplement was an important component for weight component for weight improvement and for the prevention of some respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, worker bees use pollen for royal jelly production (basic food for the larval queen and worker larvae) or directly as food due to the great amount of proteins and lipids present in it [2]. As it immensely benefits the insects' diet, pollen has become an important component of animal feed, above all, as an exceptional source of proteins and a good natural substitute for antibiotics [3]. Regarding pollen as food for humans, the first review was probably presented in the 70s; the authors [2] had reviewed the currently available data and concluded that for some athletes from different countries pollen as a dietary supplement was an important component for weight component for weight improvement and for the prevention of some respiratory infections.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, due to the increased awareness of consumers that the consumption of functional foods can improve their health, pollen began to be considered as a functional food and feed ingredient. So far, a number of fermented pollen-based food products have been developed , including bee-collected pollen-based baking [40,41], and confectionery [42,43], juice [44], and meat [45][46][47] food products; the dietary use of bee pollen as a feed additive for livestock and poultry revealed that bee pollen improves growth, reproductive, and immune performance of animals [3,[48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Good nutrition must be provided to maintain health (Abdelnour, Abd El-Hack, Alagawany, Farag, & Elnesr, 2019;Alagawany et al, 2019;Elnesr, Ropy, & Abdel-Razik, 2019). Prebiotic and probiotics were used to feed medication to improve feed intake and digestion (Abd El-Hack, Mahgoub, Alagawany, & Ashour, 2017;Alagawany et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This natural product is considered a health food, as it exhibit a wide range of therapeutic properties, including: antioxidant, antimicrobial, antifungal, hepatoprotective, and anti-inflammatory activities; for detailed review see [2]. The very recent review lists numerous positive effects of bee pollen supplementation on poultry, showing that dietary bee pollen inclusion may exert positive immunomodulatory effects, antioxidants effects, anti-inflammatory effects, improve blood profile and biochemistry, improve cardiac, liver and kidney functions [3].…”
Section: Introductionmentioning
confidence: 99%